Impact of new coalbed methane wells on old well productivity and its controlling factors: a case study of Shizhuangnan block in Qinshui Basin - Xueting HAN; Shangzhi MENG; Guangjing LIU; Zhenyu REN; Shu TAO; Xinyang MEN; Ziyang WEI (Shiyou shiyan dizhi)
To address the issue of uneven productivity release in the Shizhuangnan block of the Qinshui Basin, the initial well pattern is optimized through horizontal well infill to enhance reservoir utilization. However, frequent occurrences of drilling mud and fracturing fluid migration to neighboring wells have resulted in varying degrees of effect to old well productivity. Based on the coalbed methane development in the Shizhuangnan block, the study analyzed the main causes for well-to-well interference and its impact on productivity. From the geological and engineering perspectives, countermeasures and suggestions on well deployment were proposed. The results revealed that staged fracturing of new horizontal wells is the primary cause impairing old well productivity. The proportion of wells affected by drilling is relatively low, with poor productivity recovery efficiency. The impact from fracturing is predominantly concentrated near the wellbore (minimum well spacing < 120 m). The minimum well spacing for fracturing-affecting wells generally ranges from 120 to 300 m, with impact observed at burial depth between 550 to 900 m. The abnormal production in affected wells is characterized by the height increase in liquid water column. Some old wells, with a minimum well spacing of less than 150 m or developed tectonic coal, experience black water production and pump shutdowns. Wells with these issues exhibit lower recovery efficiency. While the production can be significantly restored by manual real-time unclogging, failure in unclogging results in a substantial decrease in gas production. Old wells affected by new well fracturing are distributed in the perforation direction of the horizontal section of new wells. Geologically, the distribution is mainly controlled by the anisotropy of horizontal principal stress. There are two propagation mechanisms depending on well spacing: hydraulic fracture communication and fracturing fluid front propagation. The horizontal stress difference in the coal reservoir of the Shizhuangnan block ranges from 5.5 to 13.5 MPa, with the average horizontal stress difference in the fracturing-affected wells greater than 10 MPa. Under high horizontal stress differences, the strong orientation of hydraulic fractures disturbs the fluid field of the old wells. To mitigate the impact, the deployment of new wells should maintain a minimum well spacing of over 300 m to the old wells and avoid faults. In areas with high stress differences, temporary plugging and diverting fracturing, reducing spacing between clusters, and enhancing stress interference between fractures can be employed to mitigate the fracturing impact on old well productivity.